The role of antimicrobial stewardship in preventing KPC-producing Klebsiella pneumoniae. (27th January 2021) - Carrara, Elena; Conti, Michela; Meschiari, Marianna; Mussini, Cristina
Abstract: Antimicrobial stewardship programmes are widely considered to be a core component of the response to the antimicrobial resistance threat. However, a positive impact of these interventions in terms of microbiological outcomes remains difficult to demonstrate, especially when focusing on specific resistant phenotypes. The first part of this review aims to explore the complex relationship between antibiotic exposure and resistance development in KPC-producing Klebsiella pneumoniae . In the second part we aim to summarize published examples of antimicrobial stewardship interventions intended to impact on the epidemiology of KPC-producing K. pneumoniae . For this purpose, a literature search was performed and seven studies were included in the review. Both restrictive and non-restrictive interventions were associated with an overall reduction in antibiotic consumption, and a decrease in carbapenem resistance rates was observed in five studies. The overall quality of the evidence was low, mainly due to the poor reporting of microbiological outcomes, lack of a control group and suboptimal study design. Although the link between antibiotic use and resistance development is supported by strong evidence, demonstrating the impact of antimicrobial stewardship interventions on microbiological outcomes remains difficult. Studies with adequate design and appropriate outcome measures are needed to further promote antimicrobial stewardship and elucidate which interventions are more successful for controlling the spread of KPC-producing K. pneumoniae .